2013
DOI: 10.1051/swsc/2013025
|View full text |Cite
|
Sign up to set email alerts
|

Space weather challenges of the polar cap ionosphere

Abstract: This paper presents research on polar cap ionosphere space weather phenomena conducted during the European Cooperation in Science and Technology (COST) action ES0803 from 2008 to 2012. The main part of the work has been directed toward the study of plasma instabilities and scintillations in association with cusp flow channels and polar cap electron density structures/patches, which is considered as critical knowledge in order to develop forecast models for scintillations in the polar cap. We have approached th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
194
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(203 citation statements)
references
References 109 publications
(140 reference statements)
9
194
0
Order By: Relevance
“…Investigations of density depressions can be regarded as a complementary effort to studies of production and evolution of plasma enhancements such as polar patches [Crowley et al, 1993]. In this sense, the current study complements well the recent experimental studies of polar patches that were enabled by expanding capabilities to image the polar cap using radio and optical techniques [e.g., Hosokawa et al, 2009Hosokawa et al, , 2014Oksavik et al, 2010;Dahlgren et al, 2012b;Moen et al, 2013;Zhang et al, 2013;Burston et al, 2014;Nishimura et al, 2014]. Moreover, the current study also focused on series of propagating density enhancements in the vicinity of density depressions and can therefore be regarded as complementary to both of these broader efforts.…”
Section: Discussionsupporting
confidence: 63%
“…Investigations of density depressions can be regarded as a complementary effort to studies of production and evolution of plasma enhancements such as polar patches [Crowley et al, 1993]. In this sense, the current study complements well the recent experimental studies of polar patches that were enabled by expanding capabilities to image the polar cap using radio and optical techniques [e.g., Hosokawa et al, 2009Hosokawa et al, , 2014Oksavik et al, 2010;Dahlgren et al, 2012b;Moen et al, 2013;Zhang et al, 2013;Burston et al, 2014;Nishimura et al, 2014]. Moreover, the current study also focused on series of propagating density enhancements in the vicinity of density depressions and can therefore be regarded as complementary to both of these broader efforts.…”
Section: Discussionsupporting
confidence: 63%
“…r / that were computed over one minute intervals are used in this study. Notable amplitude scintillations seldom occur in the high latitudes (Spogli et al 2009;Li et al 2010;Prikryl et al 2010;Moen et al 2013), and in the time period of our interest, the amplitude scintillation indices were mostly at the noise level (S 4 is below or around 0.05), thus we focus on the phase scintillation in this study. Figure 1a shows a keogram of the 630.0 nm emissions scanned from the ASIP along the geomagnetic North-South cross section.…”
Section: Observationsmentioning
confidence: 99%
“…It is well known that both polar cap patches and auroral particle precipitations can develop small scale ionospheric irregularities (Tsunoda 1988;Basu et al 1990); these irregularities can scatter radio signals and give rise to scintillations. In recent years, more GPS scintillation monitors have been deployed at high latitudes, and several statistical and case studies of high latitude GPS scintillations have been conducted (De Franceschi et al 2008;Spogli et al 2009;Li et al 2010;Alfonsi et al 2011;Prikryl et al 2010Prikryl et al , 2011Prikryl et al , 2013Moen et al 2013;Jiao et al 2013). Mitchell et al (2005) found phase and amplitude scintillations to be colocated with strong gradients in the Total Electron Content (TEC) at the edges of the high electron density streams.…”
Section: Introductionmentioning
confidence: 99%
“…With a growing number of GNSS Ionospheric Scintillation and TEC Monitors (GISTMs) operating at high latitudes, it has become possible to build a detailed scintillation climatology from accumulated scintillation data in the auroral and polar regions (Spogli et al, 2009;Li et al, 2010;Alfonsi et al, 2011;Prikryl et al, 2011a;Moen et al, 2013). Spogli et al (2009) and Alfonsi et al (2011) were the first to describe the essence of what they called the "GroundBased Scintillation Climatology (GBSC)" method, laying down the basis how to obtain maps, in geographic and geomagnetic coordinates, of scintillation occurrence and total electron content (TEC) variations observed by a network of GISTMs, to investigate dependencies on interplanetary magnetic field (IMF) orientation, geomagnetic activity and season and solar cycle.…”
Section: Introductionmentioning
confidence: 99%